2010
DOI: 10.2478/cmam-2010-0012
|View full text |Cite
|
Sign up to set email alerts
|

Computation of the Hartree-Fock Exchange by the Tensor-Structured Methods

Abstract: -We propose a novel numerical method for fast and accurate evaluation of the exchange part of the Fock operator in the Hartree-Fock equation which is a (nonlocal) integral operator in R 3 × R 3 . Usually, this challenging computational problem is solved by analytical evaluation of two-electron integrals using the "analytically separable" Galerkin basis functions, like Gaussians. Instead, we employ the agglomerated "grey-box" numerical computation of the corresponding six-dimensional integrals in the tensor-str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…In particular, the opportunity to verify the results of the 3D grid-based tensor approach by comparison with the 3D calculations by analytical methods of high accuracy using a standard package [44] helped to convince the scientific community [23,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the opportunity to verify the results of the 3D grid-based tensor approach by comparison with the 3D calculations by analytical methods of high accuracy using a standard package [44] helped to convince the scientific community [23,21].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it became possible to avoid the cubic scaling of computational work in the numerical treatment of functions and operators in 3D problems. The tensor-structured numerical methods for the 3D grid-based calculation of the Coulomb and exchange integral operators have been introduced in [23,21,22], when it was shown that the 3D convolution integration can be reduced to tensor calculus based on combinations of 1D convolutions, and 1D Hadamard and scalar products.…”
Section: Introductionmentioning
confidence: 99%
“…Tensor numerical methods are proved to be efficient for data-sparse representation of functions and operators in the Hartree-Fock and Kohn-Sham models in electronic structure calculations [7,39,59,57,23,76,47]. Fully tensorized numerical approach for solving the Hartree-Fock equation, discretized over N × N × N grid, by tensor truncated iteration of complexity O(N log N ), was recently presented in [58].…”
Section: On Tensor-structured Solution Of Multidimensional Equationsmentioning
confidence: 99%
“…The exchange matrix K(C) is computed in three steps, see [23,24]. For a = 1, ..., N orb , and ν = 1, ..., N b , compute the convolution integrals,…”
Section: Computation Of the Exchange Matrixmentioning
confidence: 99%
“…• tensor calculation of the Coulomb and exchange integrals in R 3 by means of a combination of 1D Hadamard and scalar products and 1D convolutions [30,23,24].…”
Section: Introductionmentioning
confidence: 99%